Experimental study on structural performance of flow drilled connections in HSS members. (January 2020) - Dhanapal, Jothiarun; Das, Sreekanta; Ghaednia, Hossein; Bell, Michael
Abstract: Bolted connections used for connecting hollow structural steel (HSS) members are often made using bolts which have access to the HSS member from only one face. Hence, no nuts can be used in these connections. Such connections are often called as one-sided connection. Flow drilling and flow tapping techniques has the potential to make such one-sided bolted connections with relative ease. This paper presents outcomes of a study completed to determine the structural behavior of flow drilled connections made on HSS sections. The connections considered in this study were tested in tension and shear. A total of 150 tests of which 75 in tension and 75 in shear were completed. The effect of four different parameters namely HSS section geometry, screw hole drilling technique, tapping technique, and number of screw threads per unit length were considered. In all the connections considered in this study the diameter of the screw hole was kept unchanged at 19.05 mm (0.75 in). This study showed that the tension capacity of the one-sided connections can be increased to 95% by using flow drilled connections as it offers more number of threads for screw engagement. This study also showed that the flow drilling does not have significant influence on the shear behavior of the connections. Potential failure modes were identified. Analytical equations were developed to aid in the design of these connections. Highlights: This paper presents the performance of flow drilled connections. This paper highlights the potential of flow drilling to increase the tension load capacity. This paper shows the benefit of flow tapping over standard tapping in connection capacity. This paper presents different failure modes possible in flow drilled connections. This paper presents the analytical equations to aid in the design of flow drilled connections.